Importance of molecular genetic analysis in the diagnosis and classification of congenital hypothyroidism - Targovnik, Hector Manuel (2014)
Congenital hypothyroidism (CH) is the most frequent endocrine disease in infants, with the prevalence ratio in the range of 1:2,000–1:4,000 newborns.